2022
DOI: 10.3389/fpsyg.2022.1061327
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and associated factors among Palestinian advanced cancer patients: A cross-sectional study

Abstract: ObjectiveThere is limited research exploring the experiences of people living with advanced cancer in the Gaza Strip (GS), Palestine. Thus, this study aimed to determine the level of psychological distress, anxiety, and depression among advanced cancer patients in the GS and identify factors associated with a high level of distress.Materials and methodsA secondary analysis was performed using primary data from a larger study focusing on supportive care needs in advanced cancer patients in GS. Three hundred six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Lung cancer is the second most commonly diagnosed cancer in Palestine, comprising 11.4% of the total cancers ( 58 ). The fragile Palestinian HCS, shortage of healthcare professionals ( 59 ), and limited resources impede achieving optimal cancer services and meeting the needs of cancer patients, including lung cancer ( 60 , 61 ). Furthermore, Palestinian patients with lung cancer are unfortunately diagnosed at a late stage, and they experience shortness of breath, coughing up blood, and severe chest pain ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is the second most commonly diagnosed cancer in Palestine, comprising 11.4% of the total cancers ( 58 ). The fragile Palestinian HCS, shortage of healthcare professionals ( 59 ), and limited resources impede achieving optimal cancer services and meeting the needs of cancer patients, including lung cancer ( 60 , 61 ). Furthermore, Palestinian patients with lung cancer are unfortunately diagnosed at a late stage, and they experience shortness of breath, coughing up blood, and severe chest pain ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hammoda Abu-Odah and colleagues (2022) studied in 366 cancer patients and found that the main causes of distress include: physical concerns (n = 355, accounting for 98.3%), emotional concerns (n = 341, accounting for 94.5%) and practical concerns (n = 308, accounting for 85.3%) [8]. In Jennifer Smith's study: out of 290 screenings with DT score ≥ 4, 109 were related to practical concerns (treatment decisions: 23%; insurance -finance: 23%; transportation: 22%; workplace -school: 19%; housing: 19%); 75 turns related to family issues; 206 visits were related to emotional problems (including 39% anxiety, 35% depression, 28% fear and 2% sadness) [4].…”
Section: Score Of Distress and Source Of Distressmentioning
confidence: 99%
“…Cancer survivorship, defined as living with the challenges of cancer diagnosis and treatment, has significant emotional and social implications ( Cohen, 2014 ; Goldblatt et al, 2016 ; Granek et al, 2019 ; Abu-Odah et al, 2022 ). Furthermore, BC, a disease predominantly affecting women, presents distinctive challenges in terms of their psychological well-being.…”
Section: Introductionmentioning
confidence: 99%